Um estudo sobre a evolução da leucemia mielóide crônica: período de 2000/2004 - GONÇALVES, Ana Carolina Azevedo (2023)
The objective this research was evaluate the evolution of the chronic myelogenous leukemia, given more attention for analysis of the disease stages, chronic and acute, for treatments and epidemiology of disease. The patients that received the diagnosis of chronic myelogenous leukemia in Ophir Loyola Hospital from January 2000 to December 2004 and have Philadelphia chromosome positive and/or gene BCR/ABL positive are the sample, 45 patients. The information were collected in the medical records, revealing: majority masculine, 55,6% (25/45); median age at presentation was 42 years, and 28,9% (13/45) of the patients were from 31 to 40 years on diagnosis; 55,5% (25/45) lived in Belem; 56% (24/43) had more than 50.000 leukocytes on first consultation; median duration between chronic stage to acute stage was 23,4 months and from acute stage to blast crisis was 28 months; 36% (16/45) of the sample dead , 20% (9/45) continued the treatment BCR/ABL positive, 7% (3/45) continued treatment BCR/ABL negative and 37% (17/45) did not have continuation of the medical records; only 7 % (3/45) of the patient did bone marrow transplantation, that is only definitive treatment. The research disclosed the patients profile with chronic myelogenous leukemia in region and showed that age at presentation of the disease in region is smaller than international literature and that the mortality is high. In spite of a inferior median age, the percentage of bone marrow transplantation is low.